Maneuvering through the crisis: Labor market and social policies during the COVID-19 pandemic - Werner Eichhorst; Paul Marx; Ulf Rinne (Institute of Labor Economics (IZA), 2020)
The unprecedented COVID-19 pandemic has a severe impact on societies, economies and labor markets. However, not all countries, socio-economic groups and sectors within all countries are equally affected. Part of this difference can be related to the different role and extent of short-time work, which is now being used more widely than during the Great Recession. Some countries have created or expanded such schemes, making coverage less exclusive and benefits more generous, at least temporarily. But short-time work is certainly not a panacea to "flatten the unemployment curve" - especially not in a scenario of a longerterm crisis with broad economic impacts on a global scale. Furthermore, next to providing liquidity support to firms, unemployment benefits have been made more generous in many countries. Often, activation principles have also been temporarily reduced. Some countries have increased access to income support to some extent also for non-standard workers, such as temporary agency workers or self-employed workers, on an ad hoc basis. While it is still too early to assess the relative success of national strategies to cope with the pandemic and to revitalize the labor market as well as to evaluate the medium-term fiscal viability of different support measures, a few policy directions become apparent. These include the use of digital tools to increase resilience against economic shocks (also in areas such as education and for the provision of public services), the longer- term perspective of shorttime workers in the current crisis, social protection for self-employed workers that is robust to economic crises, and resilient models for school-to-work transitions of younger workers.
Keywords: J68; O57; H12; 330; COVID-19; pandemics policy; short-time work; unemployment; economic crisis